2011
DOI: 10.1177/0885728811415098
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of Accommodations in High School and College

Abstract: Although more students with disabilities are attending college than ever before (Dukes & Shaw, 1999; Henderson, 2001), they are much less likely to graduate from college than their peers without disabilities (Horn & Bobbitt, 1999; National Council on Disability, 2003). This lower graduation rate for young adults with disabilities is of great concern given that there is a growing demand for a highly educated workforce and a corresponding decrease in jobs available to those who are not college educated (Kazis et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 22 publications
(34 reference statements)
4
31
0
2
Order By: Relevance
“…In this researcher's experience as a university career services provider, communication with career services office staff and prospective employers was identified to be a major barrier to students' utilization of accommodations. Many employers, although familiar with the legal implications of Section 504, may not see the need to provide alternative job opportunities for SWPDs, which adds to the difficulty these students may experience in discussing accommodations with potential employers (Bolt et al 2011). In essence, this study also shows the relationship between services and programs available to SWPDs and the information and education provided to the students regarding said services.…”
Section: Study Frameworkmentioning
confidence: 93%
See 4 more Smart Citations
“…In this researcher's experience as a university career services provider, communication with career services office staff and prospective employers was identified to be a major barrier to students' utilization of accommodations. Many employers, although familiar with the legal implications of Section 504, may not see the need to provide alternative job opportunities for SWPDs, which adds to the difficulty these students may experience in discussing accommodations with potential employers (Bolt et al 2011). In essence, this study also shows the relationship between services and programs available to SWPDs and the information and education provided to the students regarding said services.…”
Section: Study Frameworkmentioning
confidence: 93%
“…Students who share personal characteristics with populations that do not have long histories of success in education may be considered at risk for failure in college (Schreiner, Noel, Anderson, & Cantwell, 2011). Researchers have also noted that SWPDs experience a higher attrition rate than their peers without disabilities (Bolt et al, 2011), likely due to the presence of an impairment that limits their life activities and affects persistence to graduation (Adams & Proctor, 2010). In their longitudinal study, Berkner, Curraro-Alamin, McCormick, and Bobbit (1996) found that students with disabilities experienced a graduation rate ten percent lower than their peers without disabilities.…”
Section: Findings From the 2006mentioning
confidence: 99%
See 3 more Smart Citations